OPTIMALISASI PENJADWALAN PERAWAT SIKLIK MENGGUNAKAN INTEGER NON-LINEAR PROGRAMMING DI RUMAH SEHAT TERPADU DOMPET DHUAFA PARUNG, BOGOR - Maya Widyastiti; Lestari Dwi Asih (Universitas Pakuan, 2015)
One of problems that frequently occursin hospital management is nurses scheduling problem. A suitable schedule is needed in order to avoid fatigue, both physically and psychologically, which subsequently may deteriorate their performance. Nurse scheduling is commonly designed by the head of nurse manually. In this research, a cyclical nurse scheduling problem is modeled in the form of an integer non-linear programming. The objective of the model is to minimize the number of nurses which works for 30 days. Then optimization problem is implemented to nurses scheduling in the Rumah Sehat Terpadu Dompet Dhuafa Parung Bogor.Key words : Integer Non-Linear Programming, Optimasi, scheduling cycle